2000
DOI: 10.1002/(sici)1096-9837(200002)25:2<145::aid-esp51>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of interrill erosion under �different slopes and plot sizes

Abstract: Despite numerous studies, the effect of slope on interrill erosion is not clearly established. Several interactions exist between erosion parameters that are not taken into account under experimental laboratory measurements and results need to be validated in the field. The influence of slope steepness (2 to 8 per cent) on soil loss for a crusted interrill area and the detachment and transport processes involved in the interaction between slope, rain characteristics and plot size were investigated. Sediment di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 23 publications
6
79
1
3
Order By: Relevance
“…Secondly, the lower values for the plots compared to catchment scales can be explained by the plot length: the flow is not able to gain enough energy for effective sediment transport. Chaplot and Le Bissonais (2000) explain the transport-limited conditions of small plots as due to reduced rain impacted flow and limited flow velocity. Furthermore at both plot scales (1 m 2 and 30 m 2 ) temporal exhaustion of sediment can occur during the events, as was demonstrated by Puigdefábregas et al (1999).…”
Section: Differences In Soil Loss Derived From Replicate Soil Erosionmentioning
confidence: 70%
“…Secondly, the lower values for the plots compared to catchment scales can be explained by the plot length: the flow is not able to gain enough energy for effective sediment transport. Chaplot and Le Bissonais (2000) explain the transport-limited conditions of small plots as due to reduced rain impacted flow and limited flow velocity. Furthermore at both plot scales (1 m 2 and 30 m 2 ) temporal exhaustion of sediment can occur during the events, as was demonstrated by Puigdefábregas et al (1999).…”
Section: Differences In Soil Loss Derived From Replicate Soil Erosionmentioning
confidence: 70%
“…The reason for this difference is probably because of the quick convergence of runoff from the slope (10°) in our study. Chaplot and Le Bissonnais (2000) and Fang et al (2008) found also that the larger slope gradient could lead to higher flow velocity and increased runoff generation capacity. Similar temporal patterns were shown between TSS and TP.…”
Section: Temporal Changes In Pollution During Rainingmentioning
confidence: 95%
“…In addition, for No. 5 plot, its larger slope gradient and lower position on the slope surface could lead to larger flow velocity and higher soil moisture content downslope and leave less time to infiltrate into the soil that increased runoff generation capacity (Chaplot and Le Bissonnais 2000).…”
Section: Effect Of Slope Gradientmentioning
confidence: 99%